2021
DOI: 10.1186/s12864-021-07430-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome dynamics in early in vivo developing and in vitro produced porcine embryos

Abstract: Background The transcriptional changes around the time of embryonic genome activation in pre-implantation embryos indicate that this process is highly dynamic. In vitro produced porcine blastocysts are known to be less competent than in vivo developed blastocysts. To understand the conditions that compromise developmental competence of in vitro embryos, it is crucial to evaluate the transcriptional profile of porcine embryos during pre-implantation stages. In this study, we investigated the tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…In all, 10,542 and 10,518 genes had at least 1 count per million reads (CPM) after TMM normalisation and correction for batch effect in ICSI- and mICSI-derived blastocyst RNAseq data, respectively (Additional file 2 : Table S7). This indicates the number of genes expressed in blastocysts and is comparable to other reports [ 28 , 47 ].…”
Section: Resultssupporting
confidence: 91%
“…In all, 10,542 and 10,518 genes had at least 1 count per million reads (CPM) after TMM normalisation and correction for batch effect in ICSI- and mICSI-derived blastocyst RNAseq data, respectively (Additional file 2 : Table S7). This indicates the number of genes expressed in blastocysts and is comparable to other reports [ 28 , 47 ].…”
Section: Resultssupporting
confidence: 91%
“…The transcriptome characteristics of the zygotic genome in mice and humans have been reported [ 25 , 30 ]. Vera et al found that in vivo developed and in vitro produced porcine embryos displayed largely similar transcriptome profiles in 4-cell embryos, morulae and hatched blastocysts [ 60 ]. However, the researcher only observed embryos at three stages and no continuous evidence provided to show the global transcriptome level of porcine embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo in vitro culture (IVC), a crucial part of the IVP procedure, is a complex system that mimics in vivo conditions [ 3 , 4 ]. During IVC, embryos are cultured in controlled laboratory settings with a synthetic medium.…”
Section: Introductionmentioning
confidence: 99%